2016
DOI: 10.1002/jsc.2103
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Impact of ICT in South African SMEs

Abstract: U sing the technology-organization-environment model, this study investigates the adoption and impact of information and communications technology by small and medium-sized enterprises in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 58 publications
1
41
0
3
Order By: Relevance
“…To answer our research question, we use a mixed-method analysis (Lieberman, 2005) including qualitative semi-structured interviews and data mining. This approach is based on existing e-leadership research (Avolio et al, 2014;Bansal & Singh, 2017;Hüsing et al, 2015;Li et al, 2016;Purvanova & Bono, 2009) and the digital adoption literature (Gono et al, 2016;Van Wart et al, 2017). The semi-structured interview approach enabled us to gain a better understanding of the experiences, attitudes, values, and processes regarding the adoption of e-leadership in SMEs (Lieberman, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…To answer our research question, we use a mixed-method analysis (Lieberman, 2005) including qualitative semi-structured interviews and data mining. This approach is based on existing e-leadership research (Avolio et al, 2014;Bansal & Singh, 2017;Hüsing et al, 2015;Li et al, 2016;Purvanova & Bono, 2009) and the digital adoption literature (Gono et al, 2016;Van Wart et al, 2017). The semi-structured interview approach enabled us to gain a better understanding of the experiences, attitudes, values, and processes regarding the adoption of e-leadership in SMEs (Lieberman, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The literature review confirms that most of the studies of e-leadership in SMEs consider how SMEs adopt ICT in their businesses [14,42] though little attention has been paid to examining the e-leadership behaviours of SME leaders.…”
Section: Factors Influencing the Adoption Of Ict In The Sme Sectormentioning
confidence: 57%
“…The same foundation suggests that ICT usage factors would be better if they were being analyzed thoroughly, thus could increase the usage of ICT among the SME owners. The theme of internal factors of the company are the age of the company [20], [15], limited capital [39], [12], [7], less skilled workers [17] and family business [6], [18]. The derivation of these sub-themes indicated that the management should overcome all the problems arise hence will help to increase the ICT usage in their business.…”
Section: Discussionmentioning
confidence: 99%
“…However, the SME owner's attitude and knowledge in ICT are the key determinants of a business in accepting ICT [40]. Other factors that contribute to the low usage of ICT in SMEs are due to internal and external factors [20]. Internal factors include experience in ICT and organizational size.…”
Section: Factors Affecting Ict Usage Among Sme Ownersmentioning
confidence: 99%
See 1 more Smart Citation